Pengaruh Terapi Okupasi Membuat Handicraft terhadap Self-Esteem pada Pasien Skizofrenia - Eka Ira Putri Mardayanti; Retna Febri Arifiati (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Schizophrenia is a severe mental disorder that is often accompanied by self-concept problems, one of which is low self-esteem. Occupational therapy through handicraft activities is one of the non-pharmacological interventions that can increase a sense of accomplishment and self-esteem. Objectives: This study aims to determine and analyze the effect of occupational therapy intervention in the form of handicraft activities on increasing self-esteem in schizophrenia patients. Methods: This study used a quantitative design with a one-group pre-test post-test method. The sample consisted of 22 participants, selected based on purposive sampling. The instrument used to measure self-esteem was the Rosenberg Self-Esteem Scale (RSES). The handicraft activity intervention was given in eight sessions. Data were analyzed using a paired sample t-test. Results: This study shows an increase in self-esteem scores after the handicraft intervention, as indicated by a statistically significant difference between pretest and posttest scores with a p-value of 0.000 (p < 0.05). This indicates that the handicraft intervention has an effect on increasing self- esteem in schizophrenia patients. Conclusion: Handicraft intervention is one of the effective non-pharmacological interventions to increase self-esteem scores in schizophrenia patients. There was a significant increase in patients aged 26-35 years and in male patients compared to female patients. This intervention can be recommended for occupational therapists in mental health facilities and can be used as a reference for further research. Keywords: Occupational Therapist, Handicrafts, Self-Esteem, Schizophrenia